Inflammatory markers to predict neoadjuvant chemoradiotherapy response in rectal cancer patients - ALKIŞ, HİLAL; ADLI, MUSTAFA (My University, 2023)
Purpose or Objective Pretreatment inflammatory markers obtained from the complete blood count (CBC) can be predictive for treatment response in rectal cancer patients treated with neoadjuvant chemoradiotherapy (NACRT). The aim of this study was to determine the correlation between inflammatory markers and treatment response in rectal cancer patients treated with NACRT. Materials and Methods A total of 192 rectal cancer patients treated with NACRT were included in the study. Male/female ratio was 1.59. Clinical T stage was T2 in 13 patients, T3 in 162, and T4 in 17. Clinical N stage was N0 in 25 patients, N1 in 160, and N2 in 7. Radiation dose was 50-56 Gy to the primary tumor and 45-50.4 Gy to the regional lymph nodes. All patients received concurrent capecitabine (n=191) or 5-fluorouracil (n=1). Patients with no evidence of residual disease on DRE, MRI, and endoscopic evaluation following NACRT were determined as clinical complete responders. Patients with clinical (n=34) or pathological (n=27) complete response were classified as complete responders (CR) and the other response groups as non- complete responders (nCR) (n=131). Pretreatment absolute values of neutrophils (N), lymphocytes (L), monocytes (M), and platelets (P), plateletcrit (PCT), mean platelet volume (MPV), neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to- monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR) were recorded as hematological inflammatory markers. Mann– Whitney U-test was used to compare the variables between the groups. Results Median age was 60 (18-86) years. Mean N, NLR, PLR, L, and LMR are given in the Table. Pretreatment N (p=0.042), NLR (p=0.001), and PLR (p=0.002) were significantly higher, while L (p=0.015) and LMR (p=0.004) were lower in nCR group compared to CR group. Pretreatment M, P, PCT, and MPV did not have any effect on the treatment response. Table. Mean (± SD) N, L, NLR, PLR, and LMR values according to treatment response. Markers Neutrophil (103/μL) Lymphocyte (103/μL) NLR PLR LMR Conclusion CR nCR 4.65 ± 1.41 5.21 ± 1.70 2.86 ± 4.85 1.99 ± 0.71 2.27 ± 1.05 3.03 ± 1.62 P value 0.042 0.015 0.001 0.002 0.004 130.36 ± 58.51 4.71 ± 4.85 164.20 ± 77.92 3.55 ± 1.62 Rectal cancer patients with lower pretreatment N, NLR, PLR, and higher L and LMR are more likely to have complete response following NACRT. These markers may be used to predict treatment response in rectal cancer patients treated with NACRT.
Keywords: Tıp; Dahili Tıp Bilimleri; Radyasyon Onkolojisi; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Radiation Oncology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji ve Ultrason Teknolojisi; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Radyoloji, Nükleer Tıp ve Görüntüleme; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Radiological and Ultrasound Technology; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Radiology, Nuclear Medicine and Imaging; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine